A Comparative Evaluation of the Effect of Prone Positioning Methods on Blood Loss and Intra-Abdominal Pressure in Obese Patients Undergoing Spinal Surgery - Kundra, Sandeep; Bansal, Hanish; Gupta, Vishnu; Gupta, Rekha; Kaushal, Sandeep; Grewal, Anju; Chaudhary, Ashwani K. (Journal of Neuroanaesthesiology and Critical Care, 2020)
Background Improper prone positioning of obese patients for spine surgery can increase the intra-abdominal pressure (IAP), resulting in increased bleeding from epidural venous plexus. The choice of prone positioning frame can be an important determinant of the IAP.Materials and Methods This prospective, randomized study was performed on obese patients (body mass index ≥ 30) scheduled for lumbar laminectomy. After administration of general anesthesia, patients were positioned prone either on Wilson’s frame (group W), or on horizontal bolsters (group H). IAP was recorded at three intervals: (1) in supine position, (2) 10 minutes after prone positioning, and (3) in prone position at the end of surgery. Intraoperative blood loss was measured quantitatively and assessed subjectively by the surgeon.Results A total of 60 patients were enrolled with 30 patients in each group. IAP in supine position was similar in both groups. However, IAP 10 minutes after prone positioning was significantly higher at 11.44 ± 1.61 mm Hg in group W as compared to 9.56 ± 1.92 mm Hg in group H (p = 0.001). Similarly, IAP of 12.24 ± 1.45 mm Hg in group W, measured on completion of surgery was significantly higher than  9.96 ± 2.35 mm Hg in group H (p = 0.001). Mean total blood loss of 440.40 ± 176.98 mL in group W was significantly higher than 317.20 ± 91.04 mL in group H (p = 0.003).Conclusion Obese patients positioned prone on Wilson’s frame had significantly higher IAP and blood loss compared to patients positioned on horizontal bolsters.
Keywords: prone position; spinal fusion; spine surgery; intra-abdominal pressure; Wilson’s frame